Epigenetic Regulation and Its Therapeutic Potential in Pulmonary Hypertension - Wang, Yu; Yan, Lingling; Zhang, Ziming; Prado, Eric; Fu, Linchen; Xu, Xuefeng; Du, Lizhong (Frontiers in Pharmacology, 2018)
Abstract: Recent advances in epigenetics have made a tremendous impact on our knowledge of biological phenomena and the environmental stressors on complex diseases. Understanding the mechanism of epigenetic reprogramming during the occurrence of pulmonary hypertension (PH) is important for advanced studies and clinical therapy. In this article, we review the discovery of novel epigenetic mechanisms associated with PH including DNA methylation, histone modification, and noncoding RNA interference. In addition, we highlight the role of epigenetic mechanisms in adult PAH resulting from undesirable perinatal environments— Extrauterine growth restriction (EUGR) and Intrauterine growth retardation (IUGR). Lastly, we give a comprehensive summary for the remaining challenges and discuss future methods of epigenetic targeted therapy for pulmonary hypertension.